Considering self‐interests and symbolism together: How instrumental and value‐expressive motives interact to influence supervisors' justice behavior. Issue 2 (4th December 2017) - Qin, Xin; Ren, Run; Zhang, Zhi‐Xue; Johnson, Russell E.
Abstract: Drawing upon functional theories of attitudes and the organizational justice literature, the current research suggests that people's attitudes toward justice likely serve an instrumental function (grounded in self‐interest, rewards maximization, and punishment minimization) as well as a value‐expressive function (grounded in the expression of self‐concept and values). Importantly, these two functions co‐exist and interact to influence supervisors' justice behavior and the consistency of such behavior via supervisors' justification for unjust behavior. Findings from a set of experimental and correlational studies confirmed these predictions. The positive effects of supervisors' value‐expressive function on justice behavior and its consistency were stronger when their instrumental function was lower (vs. higher), and justification for unjust behavior mediated these effects. Also, supplementary analyses showed that the consistency of supervisors' justice behavior positively predicted subordinates' overall justice perceptions beyond the effects of the overall level of justice behavior. We conclude by discussing the theoretical and practical implications of these findings.